The Use of Word Wall-Based Educational Games to Improve Learning Motivation of Informatics Education Students - Pua Lapu, Dian Isti Arini; Sogen, Maria Magdalena Beatrice; Punuf, Herlina Novitha; Todo, Lenny Mariana Seran (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Advances in technology have encouraged the integration of digital media in the learning process. In this study, researchers utilized educational games based on Wordwall available through the wordwall.net platform. The purpose of this study was to evaluate the effect of using the Wordwall educational game on increasing students' learning motivation. The research method used was descriptive qualitative with 30 sixth semester students from the Informatics Education Study Program at Citra Bangsa University as subjects. A questionnaire was used as a data collection instrument to obtain information on the level of students' learning motivation after using the Wordwall learning media. The results showed that the implementation of Wordwall-based educational games made a positive contribution to student involvement in the learning process and encouraged increased learning motivation. Thus, Wordwall can be considered as an alternative to effective and interesting learning media.